Re: Andrea Necchi, Félix Guerrero-Ramos, Paul L. Crispen, et al. Gemcitabine Intravesical System plus Cetrelimab or Cetrelimab Alone as Neoadjuvant Therapy in Patients with MIBC: Primary Analysis and Biomarker Results of SunRISe-4. J Clin Oncol. In press. https://doi.org/10.1200/JCO-25-02382 - Giuseppe Di Lorenzo; Carlo Buonerba (European Urology Oncology, 2026)
Purpose To assess whether adding fluoropyrimidine sensitized radiotherapy (CXRT) to adjuvant chemotherapy improves overall survival (OS) after curative intent resection of the pancreatic head. Methods This was a multicenter, randomized phase III, two step trial. Step 1: gemcitabine versus gemcitabine + erlotinib (previously reported). Step 2: random assignment to sixth chemotherapy cycle ± CXRT after five cycles of step 1 chemotherapy without progression. Outcomes of step 2 random assignment are reported here. Assuming 17 months median OS (chemotherapy alone), the sample size was 354 patients (hazard ratio [HR], 0.76, 80% power, one-sided α = .05, 316 OS events). OS/disease-free survival (DFS) were estimated by Kaplan-Meier and arms compared using the log-rank test. Results A total of 354 patients (median age 63, 55% male, 56% performance status, 1) were randomly assigned to chemotherapy (174) or chemotherapy + CXRT (180). Univariable median and 5-year OS (90% CIs) were 2.6 years (2.1-3.1) and 23.1% (17.7-28.6) for chemotherapy alone, and 2.3 years (2.0-2.6) and 27.9% (22.2-33.6) for chemotherapy + CXRT. The OS primary end point was not met (HR, 0.96 [90% CI, 0.79 to 1.18]; one-sided P = .38, two-sided P = .77). Chemotherapy + CXRT was associated with a trend for improved DFS (univariably; HR, 0.82 [95% CI, 0.65 to 1.03]; P = .089), without increase in grade 4/5 toxicities. However, grade 3 toxicity increased (38% v 19%, P < .001). Significantly, treatment by nodal status interactions showed that CXRT improved OS (P = .0063) and DFS (P = .014) in node-negative patients. Conclusion Overall, the addition of adjuvant CXRT to adjuvant gemcitabine did not statistically significantly improve OS, DFS, or increase grade 4/5 toxicity. For node-negative patients, CXRT improved OS and DFS. These results, if confirmed in studies with current or future systemic therapies, would support the use of adjuvant/neoadjuvant CXRT for node-negative patients.